Extracellular matrix alterations in the ketamine model of schizophrenia. (14th May 2017) - Matuszko, Gabriela; Curreli, Sebastiano; Kaushik, Rahul; Becker, Axel; Dityatev, Alexander
Highlights: The extracellular matrix was studied in the ketamine model of schizophrenia in rats. Two major defects in matrix expression were detected in the prefrontal cortex. Ketamine-treated rats show a loss of interneuron-associated WFA + perineuronal nets. Ketamine-treated rats show elevation of glial CS56 + extracellular matrix. These data are in line with and extend post-mortem human studies. Abstract: The neural extracellular matrix (ECM) plays an important role in regulation of perisomatic GABAergic inhibition and synaptic plasticity in the hippocampus and cortex. Decreased labeling of perineuronal nets, a form of ECM predominantly associated with parvalbumin-expressing interneurons in the brain, has been observed in post-mortem studies of schizophrenia patients, specifically, in brain areas such as prefrontal cortex, entorhinal cortex, and amygdala. Moreover, glial ECM in the form of dandelion clock-like structures was reported to be altered in schizophrenia patients. Here, we verified whether similar abnormalities in neural ECM can be reproduced in a rat model of schizophrenia, in which animals received sub-chronic administration of ketamine to reproduce the aspects of disease related to disrupted signaling through N-methyl-D-aspartate receptors. Our study focused on two schizophrenia-related brain areas, namely the medial prefrontal cortex (mPFC) and hippocampus. Semi-quantitative immunohistochemistry was performed to evaluate investigate ECM expression using Wisteria floribunda agglutinin (WFA) and CS56 antibody, both labeling distinct chondroitin sulfate epitopes enriched in perineuronal nets and glial ECM, respectively. Our analysis revealed that ketamine-treated rats exhibit reduced number of WFA-labeled perineuronal nets, and a decreased intensity of parvalbumin fluorescence in mPFC interneurons somata. Moreover, we found an increased expression of CS56 immunoreactive form of ECM. Importantly, the loss of perineuronal nets was revealed in the mPFC, and was not detected in the hippocampus, suggesting regional specificity of ECM alterations. These data open an avenue for further investigations of functional importance of ECM abnormalities in schizophrenia as well as for search of treatments for their compensation.